Guava market in Aguascalientes: an analysis to reduce price volatility - Ramos-Sandoval, Ivonne N.; García Salazar, J. Alberto; Borja Bravo, Mercedes; Guajardo Hernández, Lenin G.; Almeraya Quintero, S. Xochilt; Arana Coronado, Óscar A. (Revista Mexicana de Ciencias Agrícolas, 2017)
Seasonality of Guava ( Psidium guajava L.) production in the state of Aguascalientes causes price volatility. In the months of higher production, from October to January, guava prices are lower than the annual average and lead to a decrease in the producers’ profit while prices above the average price occur in the remaining months. With the objective of analyzing how some supply control actions could avoid price volatility, the income and profit of guava producers in the average year 2012-2015 (base situation) and under two scenarios were calculated: practices of agronomic management of the culture (calmeo) and storage. The results indicate that in the average year 2012-2015 the gain of the producers of Aguascalientes was 180.3 million pesos. A decrease of 8.5% in production from October to January and a 15% increase from February to September, thanks to the “calmeo”, would increase producers’ profits to 214.1 million pesos. The storage of 10% of production in the months of October to January would increase the producers’ profit to 216.1 million pesos. The two alternatives increase producer gain; however, the strong investment required to achieve storage requires the practice of calmeo to be recommended as the most favorable measure of supply control to avoid price volatility.